The role of government and markets in the strategy "Europe 2020" of the European Union: A robust political economy analysis - Jürgen Wandel (International Journal of Management and Economics, 2016)
The EU's current ten year strategy "Europe 2020" aims to set out a vision of a European social market economy for the 21st century that will promote economic growth with social and ecological attributes. This article analyzes the roles ascribed to the government and the market and the extent this role allocation is suitable to enhance growth of the European Union's member states. Based on a robust political economy framework it is argued that this new economic policy concept is in essence a technocratic approach and a form of selective interventionism. As such it suffers from three major shortcomings: (1) it underestimates the difficulties of gathering and analyzing the relevant information necessary for steering the economy in the desired direction, (2) it encourages rent-seeking rather than productive entrepreneurship, and (3) it may cause a subtle transformation of the societal order through the diminution of individual liberties. It is contended that while an interventionist policy approach meets the preferences of large parts of the population, not the least in Germany, it is unlikely to boost economic growth and employment in the EU.
Keywords: B53; D72; H77; P50; 650; European Union; economic development; robust political economy; Austrian economics